ELEVATE STUDENTS’ READING COMPREHENSION THROUGH QUESTION GENERATION SRATEGY (QGS) - Delfi Papasi; Aminah Suriaman; Afrillia Anggreni (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
The purpose of this study was to prove that the Question Generation Strategy (QGS) can develop students' reading comprehension. This research was limited in literal and inferential/interpretative understanding in descriptive texts. The researcher applied a quasi-experimental research design. The sample of this study was class VIII A as an experimental class consisted of 22 students and Vlll C as a control class of 22 students. Data collection was carried out through pre-test and post-test. The results of this study show that there is a significant increased of students’ score who were taught by using Question Generation Strategy (QGS). The increasement can be seen from the change of student qualification from previously poor to fair. Furthemore the t-count value is 5.26 while the t-table is 1.68 which means the t-count is higher than the t-table. Thus the research hypothesis is accepted. In other words, the use of the Question Generation Strategy (QGS) can develop reading comprehension of grade VIII students of SMP Negeri 7 Palu. It implies that teachers are suggested to use the Question Generation Strategy (QGS) in teaching reading comprehension, especially in the junior high school level.